Inhibition of prejunctional parasympathetic pathways by β3-adrenoceptor agonists in the isolated pig detrusor: comparison with human detrusor studies - D’Agostino, Gianluigi; Salvatore, Stefano; Calvi, Paolo; Condino, Anna Maria (Frontiers in Pharmacology, 2023)
Adrenergic receptors of the β3-subtype (β3-ADRs) seem to represent a novel target for a more effective pharmacological treatment of overactive bladder (OAB), a wide spread urinary disorder. A promising opportunity for OAB therapy might rely on the development of selective β3-ADR agonists, but an appropriate preclinical screening, as well as investigation of their pharmacological mechanism(s), is limited by poor availability of human bladder samples and of translational animal models. In this study, we used the porcine urinary bladder as experimental tool to ascertain the functions of β3-ADRs in the control the parasympathetic motor drive. Tritiated acetylcholine ([3H]-ACh), mainly originated from neural stores, was released by electrical field stimulation (EFS) in epithelium-deprived detrusor strips from pigs bred without estrogens. EFS produced simultaneously [3H]-ACh release and smooth muscle contraction allowing to asses neural (pre-junctional) and myogenic (postjunctional) effects in the same experiment. Isoprenaline and mirabegron produced on the EFS-evoked effects a concentration-dependent inhibition antagonized by L-748,337, a high selective β3-ADR antagonist. The analysis of the resultant pharmacodynamic parameters supports the notion that in pig detrusors, as well as in previously described human detrusors, the activation of inhibitory β3-ADRs can modulate neural parasympathetic pathways. In such inhibitory control, the involvement of membrane K+ channels, mainly of the SK type, seems to play a pivotal role similarly to what previously described in humans. Therefore, the isolated porcine detrusor can provide a suitable experimental tool to study the mechanisms underlying the clinical efficacy of selective β3-ADR compounds for human use.